(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
A pilot-scale sequential batch reactor (SBR) biogranular system for the treatment of actual textile wastewater was developed in this study. The reactor had a working volume of 70 L and was operated according to SBRâ€™s sequence for 24-hr cycle, which includes sequential anaerobic and aerobic reaction phases. Wastewater from two textile mills were used as feed, while sewage and pineapple wastewater were used as co-substrate. After operating the system for 60 d, 30% of the sludge had transformed into biogranules and had increased to 67% at the end of the study. The biogranules developed in the reactor have sizes ranging from 0.2 mm to 9.5 mm with a mean settling velocity of 28 Â± 7 m/hr and sludge volume index of 73.9 mL/g. At the end of the study, the system yields 92% removal of COD, but the color removal oscillated throughout the development period in the range of 50 to 70%. Although the biogranules development is much faster in lab-scale reactor under controlled environment, the findings indicate the feasibility of developing biogranules in a bigger scale reactor using actual textile wastewater and other high-strength biodegradable wastewater as co-substrate.Â